Asymptotic Formula for Eigenvalues of One Dimensional Dirac System - Ulusoy, Ismail; Penahli, Etibar (Amer Inst Physics, 2016)
In this paper, we study the spectral problem for one dimensional Dirac system with Dirichlet boundary conditions. By using Counting lemma, we give an asymptotic formulas of eigenvalues of Dirac system.
International Conference on Numerical Analysis and Applied Mathematics (ICNAAM) -- SEP 23-29, 2015 -- Rhodes, GREECE
Keywords: Dirac operator; Dirichlet condition; Counting lemma